Orientasi Kepemangkuan dalam Meningkatkan Kesehatan dan Kesadaran Spiritual di Kelurahan Tonja Kecamatan Denpasar Utara - I Gusti Agung Istri Agung Gung Istri; Ni Putu Winanti; Pande Wayan Renawati; Wayan Miartha; I Made Girinata (Sevanam: Jurnal Pengabdian Masyarakat, 2022)
Community Service aimed at the Pinandita in Tonja Village, North Denpasar District, Denpasar City which aims to improve the quality of Hindu human resources, especially the Pinandita so that later they are able to transmit and teach Hindu theology, to the wider community and provide stimulation to actively learn about ethical ethics and ceremonies and spiritual methods so that the Pinandita have more expertise in addition to being the leader of the ceremony as well as the Pinandita when carrying out their obligations to lead the ceremony. The Pinandita often feel physical fatigue, tingling, and lack of concentration after several times leading the ceremony. Likewise, the Pinandita's understanding of their existence as Pinandita and their understanding of theology is still very lacking so they are interested in learning. With this understanding, the Brahma Widya Postgraduate Masters Study Program at UHN I Gusti Bagus Sugriwa Denpasar took a study program-based Community Service in Tonja Village by inviting thirty applicants and presenting five presenters from the study program who were competent in that field. The material presented is Understanding Theology (in general and adopted in Bali), Hindu Religion Events, Ethics and governance practices, Understanding Sanskrit, Meditation. From the presentation of the material, the Pinandita felt many benefits, especially the health of the Pinandita improved by practicing Pranayama and Meditation regularly and had an impact on maximizing the implementation of the Pinandita's duties properly. Likewise, other subject matter is very useful to broaden the knowledge of the Pinandita so that they feel confident in carrying out their duties.